Lead Poisoning in Opium Abusers: A Five-year Retrospective Study - Seyedkhosro Ghasempouri; Mahbobe Hatami; Zakaria Zakariaei; Navid Khosravi; Maryam Khadir (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Lead is a metal present in nature that does not play a role in physiological processes of the body. Today, the use of lead in many materials and industries causes environmental contamination. But, the prevalence is unclear among people and the concentration of lead in the blood has never been tested in general .This study was conducted to compare clinical observations and laboratory results in patients with lead poisoning. Materials and methods: In this retrospective, descriptive cross-sectional study, the records of 99 patients admitted to the poisoning department in Ghaemshahr Razi Hospital between 2011 and 2016 were studied. None of the patients had occupational exposure to lead and all consumed opium. Results: The most common symptoms were abdominal pain (91%), constipation (54%), and weakness due to anemia (53%). The mean lead level was 95.03 mg/dl before treatment and 56.33 mg/dl after treatment, indicating the effect of chelation therapy. Conclusion: The opium sold illegally in the market could be contaminated with lead. The level of lead poisoning is different in individuals according to the concentration of lead added to the opium. Opioid users with abdominal pain, constipation, anemia, weakness, and lethargy should be tested for blood lead levels.